Ancestral knowledge and pedagogical projects with students of the Pijao ethnic group, Coyaima Tolima - Guzmán Rodríguez, Julian Steve; Rincón Soto, Idana Beroska; Sanchez Leon, Nayibe Soraya (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
Indigenous peoples have a wealth of knowledge, traditional practices, cultural forms and access to natural resources, as well as forms of collective social organization and community life that make them resilient in the face of adversity and uncertainty. Rural communities face the greatest risks of labor automation, as their economies tend to have activities with a high proportion of repetitive tasks, low economic diversification and out-migration of highly skilled labor. Preparing rural economies to face the challenges and reap the benefits of technological change is crucial to make the most of the digital age for individuals and businesses. It is necessary to develop learning management based on the Moodle platform for the improvement of teaching and learning processes in the area of technology and information technology, because in rural regions of Colombia the policies needed to realize the promises of digital technologies for growth and rural welfare are an open debate. It is necessary to recognize the existence of a traditional episteme and to analyze the plurality of knowledge in the tradition of knowledge, in the socio-cultural scenarios that are produced, in order not to continue perpetuating the forms of social, cultural and educational reproduction under a unilateral vision regarding knowledge.